1999
DOI: 10.1089/end.1999.13.241
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Replacement of Urinary Tract Segments Using Biodegradable Materials in a Large-Animal Model

Abstract: We were able to develop a reliable laparoscopic technique for both segmental ureteral and partial bladder replacement in a porcine model. With AMX and SIS replacement, regeneration of urothelium occurred in both ureter and bladder. However, functional replacement was successful only in the bladder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…When intraluminal pressure is low and there is positive intraabdominal pressure compression on the graft, the graft may collapse. These similar results had been reported in segmental esophagus, ureter, and small intestine replacement with SIS [16][17][18]. On the contrary, the PGA-PLGA copolymer had an inherited strength before the degradation of the synthetic fibers.…”
Section: Discussionsupporting
confidence: 87%
“…When intraluminal pressure is low and there is positive intraabdominal pressure compression on the graft, the graft may collapse. These similar results had been reported in segmental esophagus, ureter, and small intestine replacement with SIS [16][17][18]. On the contrary, the PGA-PLGA copolymer had an inherited strength before the degradation of the synthetic fibers.…”
Section: Discussionsupporting
confidence: 87%
“…SIS has been previously demonstrated to be an unsuccessful ureteral replacement material in a study by Shalhav et al [24]. At 12 weeks, the graft material had a stricture formation rate of 100% in the six pigs studied.…”
Section: Original Researchmentioning
confidence: 89%
“…The polarographic studies showed that the preferred substrate of bladder tissue is succinate, because of the low complex I activity in this tissue. A study in larger animals should be attempted; studies on enlarging the bladder of the dog [2,17,18] and of the pot-bellied pig [19] have already shown that this type of surgery is possible, and that histologically normal bladder tissue can be thus obtained.…”
Section: Discussionmentioning
confidence: 99%